A cross-sectional survey exploring attitudes towards provincial electronic health record implementation among clients attending the Provincial Sexually Transmitted Infections Clinic in British Columbia. (5th December 2014) - Pedersen, Heather; Taylor, Darlene; Gilbert, Mark; Achen, Melanie; Lester, Richard; Ogilvie, Gina
Abstract : Introduction: To support control of sexually transmitted infections (STI), British Columbia is exploring data sharing through a provincial electronic health record (EHR). Increased electronic data sharing among healthcare providers may be a barrier for clients of STI clinics where expectations of privacy and confidentiality are heightened. Methods: A survey to assess attitudes towards sharing of personal health information through a provincial EHR was conducted with a convenience sample of clients attending an STI clinic in Vancouver. Descriptive statistics and logistic regression were used to examine the association between the primary outcome variable, whether a client would be less likely to take the test for an STI or HIV if their clinic records were made part of a provincial EHR, and independent variables of interest. Results: A total of 1004 clients completed the survey, and 31% stated that they would be less likely to get tested for STI/HIV if their records were made part of a provincial EHR. Participants who were more likely to agree that they might avoid testing had the expectation that no other clinician would review their chart (adjusted OR (AOR)=3.55), or expected their records would not be shared beyond the clinic (AOR=2.81). Discussion: While most participants thought an EHR was acceptable, a large minority expressed that they might avoid testing if their records were made part of a provincial EHR. The introduction of a provincial EHR should be considered with caution in STI healthcare settings to ensure that screening, case detection and treatment are not negatively impacted.